Analysis Of The Level Of User Satisfaction With The Ajaib Application From The E-Service Quality Perspective Using The Importance-Performance Analysis (IPA) Method And Gap Analysis - Safitri, Annisa; Mukti Soma, Abdul (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The number of retail investors in Indonesia continues to grow, particularly in mutual fund and stock investment products. This growth is driven by the emergence of financial technology in the investment sector, which facilitates easier access for the public to open securities accounts. By the end of 2024, there were 6,381,444 stock and other securities investors in Indonesia. The increase in stock investors must be supported by high electronic service quality provided by investment applications to ensure ease of use during transactions.This study aims to assess the level of electronic service quality (e-service quality) of the Ajaib investment application. Additionally, it seeks to identify the gap between customer perceptions and expectations regarding Ajaib’s e-service quality, enabling the company to recognize which dimensions require improvement or should be maintained.This is a descriptive study with a quantitative research method. The sample was obtained using incidental sampling. Primary data was collected by distributing a questionnaire to 385 Millennial users of the Ajaib application. The data were then analyzed using Importance-Performance Analysis (IPA) and gap analysis. The results indicate that the user satisfaction level with Ajaib's e-service quality stands at 94.99% (<100%), suggesting that the application’s performance falls short of user expectations. Descriptive analysis reveals that the importance score (83.99%) exceeds the performance score (79.83%). The attribute that should be the main focus for service improvement, according to the importance-performance analysis quadrant, is ensuring that transactions on the Ajaib platform can be completed quickly.